The Influence of Tanning Method and Ph on the Morphology of Astrakhan Leather (Global Scientific Review, 2023)
The article examines the morphological structure of karakul fur depending on the type of tanning and pH of the environment. Micrographs of the cross-section, surface and hair layer of tanned karakul with glutaraldehyde in acidic, alkaline and neutral media were obtained. The process of sorption of water vapor at a temperature of 20 °C in karakul specimens, tanning with chromium salts and glutaraldehyde has been studied.